Targeting metalloproteinases in cardiac remodeling - Anestakis Doxakis; Konstantinidou Polyanthi; Tsepa Androniki; Petanidis Savvas; Zagelidou Eleni; Leontari Roubini; Raikos Nikolaos (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2019)
During the last years metalloproteinases as a family of proteases have been implicated in various human diseases and catalytic mechanisms of pathological disorders. Metalloproteinases can be divided into two subgroups, matrix metalloproteinases (MMPs) and adamalysins (ADAMs). The MMPs consist of 6 basic subgroups which are inhibited by the tissue inhibitors of metalloproteinase (TIMP), while ADAMs consists of approximately 40 members. It is confi rmed that metalloproteinases are an important factor for the cardiac remodeling process, interfering with the alteration of the cardiac structure induced by cardiac injury or increased haemodynamic load. The aim of this review is the analysis of the impact of metalloproteinases on cardiac remodeling and the factors affecting metalloproteinase activity. Metalloproteinases induce the remodeling process of the cardiac tissue in both benefi cial and detrimental ways. TIMPs and various administered pharmacological agents may limit the effectiveness of metalloproteinases, therefore interfering in cardiac remodeling.